Negotiating quality standards for effective delivery of labor and childbirth care in Nigeria and Uganda. (12th December 2017) - Oladapo, Olufemi T.; Bohren, Meghan A.; Fawole, Bukola; Mugerwa, Kidza; Ojelade, Olubunmi A.; Titiloye, Musibau A.; Alu, Francis E.; Mambya, Musana O.; Oyeneyin, Lawal; Bataale, Salim; Akintan, Adesina; Alabi, Olubunmi; et al.
Abstract: Objective: "Negotiated standards" describe a level of quality of care that is acceptable and achievable within a specific health system, based on consensus between key stakeholders. This paper presents the development of negotiated standards for effective labor and childbirth care in selected hospitals and communities in Nigeria and Uganda. Methods: A four‐step development process involving different methodologies. The process included: (1) review and synthesis of internationally recognized intrapartum clinical principles and practices; (2) primary qualitative research to assess values and preferences of women and healthcare providers, and practices that align with these preferences; (3) draft contextualization of effective and ineffective behaviors to reflect values and preferences; and (4) WHO‐mediated negotiations between relevant stakeholders, including community members, providers, and administrators. Results: The primary outcomes of this process were a comprehensive set of effective behaviors and clinical practices covering the main domains of quality of care, which are practical and easy to communicate, implement, and audit across all levels of healthcare delivery. Conclusion: The process demonstrates that health facilities and providers can be motivated to adopt standards of care that uphold the values and preferences of both service users and providers, while adhering to international best practices. Abstract : By negotiating quality standards, health facilities and providers can be motivated to adopt a standard of care that upholds the values and preferences of both users and providers, while adhering to international best practices.